2020
DOI: 10.2147/dmso.s247351
|View full text |Cite
|
Sign up to set email alerts
|

<p>Comparative Effects of Curcumin versus Nano-Curcumin on Insulin Resistance, Serum Levels of Apelin and Lipid Profile in Type 2 Diabetic Rats</p>

Abstract: Background and Purpose: Type 2 diabetes mellitus (T2DM) is characterized by insulin resistance and abnormalities in insulin production. Apelin is associated with insulin resistance. According to the anti-diabetic properties of curcumin, the purpose of this study was to compare the effects of curcumin and nano-curcumin intake on insulin resistance and serum levels of fasting blood sugar (FBS), Apelin, and lipid profile (cholesterol, triglyceride, LDL, HDL and VLDL) in T2DM rats. Materials and Methods: Forty-eig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 43 publications
2
30
0
Order By: Relevance
“…Moreover, experimental studies have proved potential therapeutic actions of polyphenol compounds on APLN levels: curcumin supplementation mitigates APLN abnormalities in diabetic rats and in obese patients [130] (Table 4).…”
Section: Apelin/apj Axis: Nutritional Interventionsmentioning
confidence: 99%
“…Moreover, experimental studies have proved potential therapeutic actions of polyphenol compounds on APLN levels: curcumin supplementation mitigates APLN abnormalities in diabetic rats and in obese patients [130] (Table 4).…”
Section: Apelin/apj Axis: Nutritional Interventionsmentioning
confidence: 99%
“…The results of this study showed that using 100 mg/kg of nano‐curcumin is more effective than 200 mg/kg, however, using 200 mg/kg body weight curcumin had more therapeutic effect. These findings are helpful for future studies (Shamsi‐Goushki et al, 2020).…”
Section: Discussionmentioning
confidence: 79%
“…In the case of each subject of the group receiving nanocurcumin treatment, it was seen that after the treatment, the level of total cholesterol, triglyceride, LDL-C, and HDL-C was substantially reduced in the serum level than that of before treatment. Shamsi et al studied the impact of various doses of nanocurcumin on the level of lipid profile present in the blood serum [ 64 ]. It was found in the study that the cholesterol, low density lipoprotein, very low-density lipoprotein, as well as triglyceride level in the serum of the diabetic rats were reduced to a great extent.…”
Section: Uses Of Nanocurcuminmentioning
confidence: 99%